Exploitasi Seks Terhadap Anak Perempuan yang Menjadi Korban Perdagangan Orang di Lokasi Prostitusi - Ruman, Yustinus Suhardi (Humaniora, 2011)
The special focus of this paper is the fenomen of girls who become sex workers. They are children under age of 18 year.  This paper will show that the girls who become sex workers were human trafficking victim for sex commercial purpose. The beneficiaries of this exploitation are their parent, pimp, and those who live around of their life in prostitution location. Data is gathered by the researcher with Institute for Community Development and Social Advocacy (ICODESA) team which advocate girls as human trafficking victims in interview, observation and discussion. Child sex workers must be claimed as Prostituted Children. Psychologically they have not been able to identify rationally every decision they take; socially and economically they are victims that structurally force themselves trapped in human trafficking. They have no education, no skills needed for industry, and they are also powerless towards patriarchal local culture.